SUSTAINABILITY OF INCLUSIVE EDUCATION DURING THE PANDEMIC - Meilania Indah Prihatiningsih; Tjut Dwi Anggraini Damcha; Syafwandi Syafwandi (Jurnal Education and Development, 2023)
This study aims to find out the conditions of the sustainability of inclusive education during the pandemic in two different schools, namely Sekolah Citta Bangsa, Bekasi, and PAUD YPJ Tembagapura, Papua. Inclusive education is a challenge in the midst of a pandemic, especially for schools, parents, and students with special needs. Teachers are challenged to design learning strategies that are able to facilitate education for children with special needs in school. The research methods in this journal use qualitative research methods. The informants in the study were class teachers, special accompanying teachers, children with special needs, and parents/guardians of students, while the students of this study were children with special needs who were in two different schools. Data collection techniques are used through interviews, documentation, and observation. Qualitative data analysis is inductive, that is, research based on the data obtained.